Measurement of compartmental pressure in a leg by Whitesides method in a Nepalese patients attending a tertiary care hospital in eastern region of Nepal - Chaudhary, Pashupati; Shrestha, BP; Yadav, DK; Khanal, GP; Rijal, R (Health Renaissance, 2017)
Background: Compartment syndrome can be a life or limb-threatening emergency. Early diagnosis is important for the prevention of disability. The clinical features are subjective in nature. Intra compartmental pressure measurement is a reliable objective method for early and accurate diagnosis of compartment syndrome. Objective: To measure the compartmental pressure in a leg by Whitesides method in Nepalese patient attending a tertiary care hospital in eastern region of Nepal. Methods: This is a cross-sectional study done over the period of three years on adult patients aged 16 years and above presenting to the Emergency Department of BPKIHS with unilateral closed tibial fracture. Total of 60 patients aged 16 years and above with closed fracture tibia were enrolled in the study. Results: Out of total study population, 40 were males and 20 females. The anterior compartmental pressure in the uninjured legs ranged between 3 mmHg and 20 mmHg. Patients from hilly areas had more compartmental pressure (range 8 to 20 mmHg) as compared to patients of plain land (range 3 to 15 mmHg). People of hilly areas have more girth of thigh and calf muscles. Conclusion: The compartmental pressure in the uninjured legs ranged between 3 mmHg and 20 mmHg with variations in different geographic location. Whitesides injection technique of compartmental pressure measurement can be useful in the promptly defect compartmental syndrome in emergency and outpatient set-ups. Health Renaissance 2015;13 (1): health.renaissance@bpkihs.edu